Sistem Informasi Geografis Pemetaan Fasilitas Kesehatan di Kabupaten Bandung - Sari, Wahyu Purnama; Firdaus, Azka Fauzan; Dzaki, Daffa Fauzan; Kurniawan, Nurul Fallah; Hidayat, Remi Maulani (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
The development of information technology has had a significant impact across various sectors, including the healthcare sector. Bandung Regency, as one of the regions with a large population, is currently facing an issue of inequality in the distribution of healthcare facilities such as midwives, community health centers (puskesmas), and clinics. This disparity has made it difficult for residents, especially those in remote and densely populated areas, to access adequate healthcare services, ultimately affecting public health quality. This study aims to address the issue of unequal distribution of healthcare facilities in Bandung Regency by designing and implementing a Geographic Information System (GIS) as a strategic solution. By utilizing GIS, healthcare facility locations can be digitally mapped, providing a more accurate representation of their distribution and helping to identify areas that require development and equitable distribution of healthcare services. GIS also enables local governments to formulate more effective, data-driven policies to improve healthcare access. The results of this study are expected not only to enhance efficiency in healthcare facility planning but also to accelerate more precise decision-making and support equitable access to healthcare services across the region. The implementation of GIS is anticipated to reduce disparities in access to healthcare facilities and improve the quality of healthcare services in Bandung Regency, potentially serving as a model for other regions facing similar challenges.